A New Species of Large Carpenter Bee, Xylocopa (Hymenoptera: Apidae), from Argentina - Lucia, Mariano (2010)
The new species Xylocopa (Neocylocopa) atamisquensis is described and illustrated from adult female and male. We designate Predio Isla Verde (28º 38` 54" S, 64º04`58" W, 120 mt) department Atamisqui in South-central Santiago del Estero Province, Argentina, as the type locality. The closest species are X. (N) mendozana and X. (N) ordinaria.